Proceedings of the Second ACM SIGCOMM Workshop on Internet Measurment - IMW '02 2002
DOI: 10.1145/637201.637238
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of link failures in an IP backbone

Abstract: Today's IP backbones are provisioned to provide excellent performance in terms of loss, delay and availability. However, performance degradation and service disruption are likely in the case of failure, such as fiber cuts, router crashes, etc. In this paper, we investigate the occurence of failures in Sprint's IP backbone and their potential impact on emerging services such as Voice-over-IP (VoIP). We first examine the frequency and duration of failure events derived from IS-IS routing updates collected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(68 citation statements)
references
References 1 publication
0
67
0
1
Order By: Relevance
“…[2]. The suppression time after the link failure is detected is two seconds and the simulated time is one year.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2]. The suppression time after the link failure is detected is two seconds and the simulated time is one year.…”
Section: Methodsmentioning
confidence: 99%
“…The steady growth in the use of Internet for business-critical applications is the primary hidden reason [1] . It has been observed that majority of the link failures are short-lived and about half of the failures last less than a minute [2] . Hence, there is a growing demand for improving network survivability in the presence of short-lived link failures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markopoulou et al [9] have made a measurement study to understand the nature of intra-domain network failures recently, in which the study is carried out based on the early work proposed by Iannaccone et al [10]. They collected IS-IS routing updates from Sprint network and classified these updates into different categories based on the update root causes, such as maintenance-caused failures, router-related failures, optical-layer-related failures and individual-link failures.…”
Section: Characteristics Of Network Failuresmentioning
confidence: 99%
“…In this paper we discuss how policy-constrained bio-inspired algorithms and processes for routing can allow a network to gracefully react to transient link failures, which are described by Iannaccone et al [2] as the primary cause of service degradation in current networks. More specifically, we specify routing algorithms and processes based on biological principles and describe how they can be integrated within a policy-based network management framework for autonomic networking.…”
Section: Introductionmentioning
confidence: 99%